Recent advances in the therapeutic management of calcium pyrophosphate deposition disease - Voulgari, Paraskevi V.; Venetsanopoulou, Aliki I.; Drosos, Alexandros A. (Frontiers in Medicine, 2024)
Calcium pyrophosphate deposition (CPPD) disease is a form of crystalinduced arthropathy that arises from the accumulation of calcium pyrophosphate crystals within joints and soft tissues. This process leads to inflammation and damage to the affected joints. It can present asymptomatically or as acute or chronic inflammatory arthritis. Risk factors and comorbidities, including prior joint injury, osteoarthritis, hereditary or familial predisposition, and metabolic diseases, should be evaluated in CPPD cases.The management of CPPD remains a challenge in the sparsity of randomized controlled trials. The lack of such trials makes it difficult to establish evidence-based treatment protocols for CPPD. This review provides an overview of the current pharmacological management of CPPD, focusing on reducing inflammation, alleviating symptoms, and preventing acute flares.Non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and colchicine are effective in managing acute CPP arthritis. Colchicine may also be used prophylactically to prevent recurrent flares. In cases where other treatments have failed, anakinra, an interleukin-1 receptor antagonist, can be administered to alleviate acute flares.The management of chronic CPP inflammatory arthritis includes NSAIDs and/or colchicine, followed by hydroxychloroquine, low-dose glucocorticoids, and methotrexate, with limited data on efficacy.Tocilizumab can be used in refractory cases. In small studies, synovial destruction using intra-articular injection of yttrium 90. To date, no disease-modifying therapies exist that reduce articular calcification in CPPD.